Non-performing loans sensitivity to macro variables: panel evidence from Malaysian commercial banks - Alizadeh Janvisloo, Mohammadreza; Muhammad, Junaina (Scientific & Academic Publishing, 2013)
Credit risk is one of the most important kinds of risk in banking sector. The relationship between business cycle and banks’ loan losses was one of the hot debates in recent economic literature especially with respect to financial stability analysis. The quality of loans can be one of the factors that limit the banks' loan supply and affect on investment spending. Although banks have a significant role in transmission of monetary policy; in the meantime their performance is strongly influenced by monetary and fiscal policies that are effective in recession and prosperity and thereby affect bank performance; in other words, macroeconomic variables can effect in/directly on banks loans quality and their transitional role. Thus policy makers and bankers are always concerned with the financial stability and are always looking for tools to better manage banks’ credit risk. One of the risk indicators that are used in literature of banks’ credit risk is Non-Performing Loans (NPL). Hence themain objective of thisstudy is to analyze relationship between banks loans quality and macroeconomic variables by using a dynamic panel data model on Malaysian commercial banking system for the 1997-2012 periods. The results show that there is a strong evidence of cyclical sensitivity of loan quality in Malaysia’s commercial banking system. Based on the results lending interest rate and FDI-net outflow (% GDP) are the most effective factors on NPL ratio with simultaneous positive effects and a reverse effect with one-year delay. It can be said that the impact of external shocks on the domestic banking system is more than internal shocks. The result of this study can be helpful to bank supervisory and economists to adjust banking system stability and economic policies.